Un militantisme aux allures de mission impossible : l’exemple du lobby républicain pro-choice, la Republican Majority for Choice - Françoise Coste (Transatlantica)
The active lobbying of the Republican Majority for Choice proves the conventional wisdom about the monolithic pro-life nature of the contemporary Republican Party wrong. The RMC is a wealthy and growing organization which has concretely helped the advancement of abortion and reproductive rights, especially at the state level. But it has remained almost completely powerless to influence the national leaders of the GOP, primarily because of the historical association between most of its top-ranking members and the Republican establishment, which prevents any credible electoral threat. Yet, an undeniable rift is widening between RMC activists and the Bush administration, as the president’s acute social conservatism and reckless spending violate the basic tenets of the social moderation and fiscal conservatism of pro-choice Republicans.